2021
DOI: 10.1101/2021.02.17.431676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor 2A protects pancreatic beta cells during endoplasmic reticulum stress while rescuing translation inhibition

Abstract: The endoplasmic reticulum (ER) stress-induced unfolded protein response (UPR) helps decide cell survival in diabetes. The alternative eukaryotic initiation factor 2A (EIF2A) has been proposed to mediate EIF2S1-independent translation during cellular stress and viral infection, but its role in cells is unknown. EIF2A abundance is high in human and mouse islets relative to other tissues, and both thapsigargin and palmitate significantly increased EIF2A mRNA and EIF2A protein levels in MIN6 cells, mouse islets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…While estrogen affects insulin biosynthesis via ERα [ 117 ], future studies will need to determine whether estrogen also allows female islets to restore protein synthesis to basal levels faster than male islets following ER stress. We currently lack this knowledge, as most studies on UPR-mediated recovery from protein translation repression use single- and mixed-sex animal groups, or cultured cells [ [119] , [120] , [121] , [122] , [123] , [124] ].…”
Section: Discussionmentioning
confidence: 99%
“…While estrogen affects insulin biosynthesis via ERα [ 117 ], future studies will need to determine whether estrogen also allows female islets to restore protein synthesis to basal levels faster than male islets following ER stress. We currently lack this knowledge, as most studies on UPR-mediated recovery from protein translation repression use single- and mixed-sex animal groups, or cultured cells [ [119] , [120] , [121] , [122] , [123] , [124] ].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, this type of study would also monitor the activity of pathways known to regulate protein synthesis repression during ER stress. For example, while we did not detect any changes in levels of phosphorylated eIF2α (also known as Eif2s1), which is known to mediate UPR-induced protein synthesis repression (75), our chosen timepoints did not overlap with the rapid changes in phospho-eIF2α following ER stress published in other studies (100,101). A more detailed time course will therefore be necessary to assess p-eIF2α levels during ER stress in both sexes, and to test a role for phospho-eIF2α in mediating differences in protein synthesis repression.…”
Section: Discussionmentioning
confidence: 69%
“…Uncharacteristic of a translation initiation factor, several studies have provided evidence that eIF2A is non-cytosolic ( Kim et al, 2011 ; Panzhinskiy et al, 2021 ; Thul et al, 2017 ; Uhlen et al, 2010 ); however, no two reports are in agreement. Unfortunately, eIF2A is not included in the Yeast GFP Fusion Localization Database ( Huh et al, 2003 ).…”
Section: Eif2amentioning
confidence: 99%
“…To our knowledge, whether this localization pattern is due to an alternate function of eIF2A, such as ribosome assembly, is not reported. Second, Panzhinskiy et al demonstrated that eIF2A co-localizes with the endoplasmic reticulum (ER) in MIN6 cells during normal physiological conditions ( Panzhinskiy et al, 2021 ). ER localization during normal conditions is uncharacteristic of a translation initiation factor since translation initiation occurs in the cytosol.…”
Section: Eif2amentioning
confidence: 99%
See 1 more Smart Citation